Catalyst supporting method for methanol steam reforming hydrogen production system - ZHANG YUFENG; ZHANG XUELIN; TUO YANJING; LIU XIAOWEI (2015)
The invention relates to a catalyst supporting method for a methanol steam reforming hydrogen production system and relates to a catalyst supporting method capable of improving the performance of a miniature methanol steam reformer. According to the catalyst supporting method, silicon carbide foamed ceramic is taken as a support, a copper-based methanol reforming catalyst as a commercial off-the-shelf product is produced into powder through ball milling, then a stable suspension is prepared from the powder, and the catalyst is supported by the foamed ceramic support with a soaking method. According to the catalyst supporting method, the adhesion amount of the methanol reforming catalyst as the commercial off-the-shelf product on the support can be increased, the conversion rate of methanol steam reforming hydrogen production can be increased, the adhesiveness of the catalyst can be improved, and influence on the performance of the miniature methanol steam reformer due to the fact that the catalyst is blown down in case of a larger airflow is avoided.